The Effect of Black Soldier Fly (Hermetia illucens) Maggot Oil Extract on Acute Incision Wound Healing in Mice (Mus musculus) - Mahardhika,; Qomariyah, Nur; Khaleyla, Firas (LenteraBio : Berkala Ilmiah Biologi, 2025)
Wound treatment is usually carried out using antiseptics or antibiotics; however, if the dosage is not appropriate, it will cause bacterial resistance and infection. Black soldier fly (Hermetia illucens) maggot oil extract has antibacterial and anti-inflammatory properties, which can speed up the wound healing process. The aim of this research was to determine the effect of administering black soldier fly maggot oil extract ointment to accelerate wound healing. Black soldier fly maggot oil extract waas made into an ointment at different concentrations using vaseline solvent. This study used 24 male mice, each induced with incision wounds, which were then divided into six treatment groups: ointment treatment groups (25%, 50%, and 75%), natural control, negative, and positive, with four repetitions. The data was analyzed using ANOVA tests (p<0.05). The results of the study showed that the administration of black soldier fly maggot oil extract on wound closure, the distribution of collagen fibres, and the number of fibroblast cells had a significant effect (p<0.05). Black soldier fly maggot oil extract at a dose of 75% was the most optimal dose for healing cut wounds, as shown by the healing percentage (45%), collagen fibres scoring value (2.8), and number of fibroblast cells (2.8).